The Role of Gender Power Imbalances in the Spread of HIV among Women in Intimate Relationships: Guidelines for Social Work Practice - Leburu-Masigo, Goitseone Emelda; Kgadima, Nathaniel Phuti (International Journal of Criminology and Sociology, 2021)
Gender power imbalances and HIV are concerns that affect women globally. Social workers are ethically committed to help people affected with HIV and thereby promote gender equality. Although the literature has documented the nexus between gender imbalances and HIV, scant research explores these problems concurrently within the social work profession. Drawing on the resource theory and gender and power theory, this article undertook a qualitative exploratory to gain insights into women's perspectives on gender power imbalances as a risk factor for HIV transmission in rural communities of Ngaka Modiri Molema District, North West Province. Purposive sampling was used to recruit participants while data was collected through semi-structured interviews. The findings demonstrate that unequal power relations between men and women in intimate relationships negatively affect women’s lives in diverse ways. This gendered impact of HIV infections for women remains intact due to the rooted gender norms that limit their ability to protect themselves against risky sexual behavior by their male partners. Disclosure of one's status remains a complex stigma attached to HIV. Social work empowerment interventions that seek to enhance equality in intimate relationships are recommended.